A new large Pliosaurid from the Barremian (Lower Cretaceous) of Sáchica, Boyacá, Colombia - María Eurídice Páramo-Fonseca; Cristian David Benavides-Cabra; Ingry Esmirna Gutiérrez (Earth Sciences Research Journal)
A new fossil MP111209-1 found in the Barremian beds of Sáchica, a town near Villa de Leiva representing the more complete skeleton found in the region is described here. After a detailed study of its morphological characteristics, it is evident that the new specimen represents a new genus and species of brachauchenine pliosaurid from Central Colombia that we named Sachicasaurus vitae gen. et sp. nov. Sachicasaurus is a large brachauchenine (almost 10 m in length) characterized by the following combination of characters: skull exceeding two meters in length,  transverse constriction in the rostrum, caniniform teeth present, pineal foramen in a very advanced position, palatines separated in the midline by the pterygoids, very short mandibular symphysis (bearing four teeth positions), reduced number of mandibular teeth (less than 20), slender hyoid bones, 12 cervical vertebrae, cervical centra showing ventral foramina, single rib facet in all cervical centra, at least 40 pre-caudal vertebrae, and ilium with a long posterior projection. Although it is difficult to clearly establish the phylogenetic position of Sachicasaurus viate within Brachaucheninae due to its combination of primitive and derived features, the morphological comparisons and the cladistic analysis show an evident phylogenetic proximity of Sachicasaurus to the Aptian-Albian genus Kronosaurus.